Social and Cultural Dynamics Revisiting the Work of Pitirim A. Sorokin - Mangone, Emiliana (SpringerBriefs in Psychology and Cultural Developmental Science,, 2018)
Marking the 50th anniversary of Pitirim A. Sorokin's death, this Brief offers a critical analysis of the renowned sociologist's theories while highlighting some of his more overlooked ones. Topics explored include cultural dynamics; the relationship between culture, society, and personality; social mobility; and the socio-cultural causality of time and space. In addition, this book updates these theories by discussing their relevance in current cultural contexts. The Brief aims to extend the work started by Sorokin on the promotion and application of "integralism", an approach that conceives the change of any sociocultural phenomena as the result of the combination of external and internal forces. It uses this method to analyse socio-cultural phenomena, propose new policy, and enhance the development of humanity from the point of view of culture. This book also discusses sociology's relationship with other sciences. In particular, it touches upon the interplay between sociology and psychology and pushes for a new scientific awareness that is transdisciplinary. The end point is a new vision of humanity and its development from a cultural context. Social and Cultural Dynamics will be of interest to social scientists, sociologists, and psychologists as well as professionals in these disciplines. .